Anesthesia for tracheal and carinal resection and reconstruction. Issue 1 (3rd February 2022) - Schieren, Mark; Wappler, Frank; Defosse, Jerome
Abstract : Purpose of review: The aim of this review is to provide an overview of current anesthetic management of tracheal and carinal resection and reconstruction. Recent findings: In addition to the traditional anesthetic approach using conventional tracheal intubation after induction of general anesthesia and cross-field intubation or jet-ventilation once the airway has been surgically opened, there is a trend toward less invasive anesthetic procedures. Regional anesthetic techniques and approaches focusing on the maintenance of spontaneous respiration have emerged. Especially for cervical tracheal stenosis, laryngeal mask airways appear to be an advantageous alternative to tracheal intubation. Extracorporeal support can ensure adequate gas exchange and/or perfusion during complex resections and reconstructions without interference of airway devices with the operative field. It also serves as an effective rescue technique in case other approaches fail. Summary: The spectrum of available anesthetic techniques for major airway surgery is immense. To find the safest approach for the individual patient, comprehensive interdisciplinary planning is essential. The location and anatomic consistency of the stenosis, comorbidities, the functional status of respiratory system, as well as the planned reconstructive technique need to be considered. Until more data is available, however, a reliable evidence-based comparison of different approaches is not possible.